DISEMINASI METODE PENGAMBILAN DAN PENGUKURAN SAMPAH RUMAH TANGGA PERKOTAAN - Dasa Aprisandi; Elisabet Merida Kristia (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
One of the problems of urban household waste management is caused by the limited availability of data generated and waste characteristics obtained through standardized methods of collection and measurement. This condition is a challenge for local governments in developing data-based waste management plans. This Community Service Activity (PKM) aims to disseminate methods of collecting and measuring urban household waste to technical apparatus and the community in order to increase technical understanding and participation in waste data collection. The implementation method is carried out through technical guidance involving Lubuklinggau City Environmental Service staff as surveyors and 250 community members as volunteers. Volunteers collected and sorted household waste at the source level for three consecutive days with the assistance of surveyors. The results of the activity showed that the dissemination of the method was able to support the improvement of technical understanding of the apparatus and community involvement in the collection and measurement of household waste in a structured manner. This activity contributes to strengthening collaboration between local governments and the community and can be an initial reference for the implementation of more systematic and sustainable household waste data collection in similar activities in the future.